Answer:
Center (h,k) is (1,-2) and radius r = 2
Explanation:
We need to find the center and radius of the circle of the given equation:
![x^2-2x+y^2+4y+1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/frxxj5pbb3u4p406bhef5kbyqx9puojdnx.png)
We need to transform the above equation into standard form of circle
![(x-h)^2 + (y-k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4eirzo410e5djazi04h0efdsewkok5jdnt.png)
where(h,k) is the center of circle and r is radius of circle.
Solving the given equation:
![x^2-2x+y^2+4y+1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/frxxj5pbb3u4p406bhef5kbyqx9puojdnx.png)
Moving 1 to right side
![x^2-2x+y^2+4y=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4xbffcfr9pyud3w63w6tosukc36uv5x5d1.png)
Now making perfect square of x^2-2x and y^2+4y
Adding +1 and +4 on both sides of the equation
![x^2-2x+1+y^2+4y+4=-1+1+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iq31ex4pan3q7dywayasvj5nhtxgzydhhh.png)
Now, x^2-2x+1 is equal to (x-1)^2 and y^2+4y+2 =(y+2)^2
![(x-1)^2+(y+2)^2=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wc4nhpzvgg8o04c7vhyn2s85ai8wsp7ert.png)
Comparing with standard equation of circle:
![(x-h)^2 + (y-k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4eirzo410e5djazi04h0efdsewkok5jdnt.png)
h = 1 , k =-2 and r =2 because r^2 =4 then r=2
So, center (h,k) is (1,-2) and radius r = 2